Nonspecific Prophylaxis of Hemorrhagic Fever with Renal Syndrome in the Republic of Bashkortostan - P. A. Mochalkin; S. V. Ryabov; A. P. Mochalkin; M. I. Shutova; A. N. Matrosov; M. A. Tarasov (Проблемы особо опасных инфекций, 2010)
Scientifically based typing of HFRS foci, ecological-epizootiological monitoring and a number of sanitary-and-hygiene, sanitary-and-technical, agrotechnical, forestry as well as deratization and disinfection measures were carried out. In addition, information-explanatory work among the population was done. That enabled to eliminate group diseases in Ufa, lower to single cases the risk of HFRS infection of the population in woodland territory and reduce average annual morbidity in the city from high to middle level.